The spinsters’ descent into stereotype in selected Malaysian and Singaporean short stories - Mohd Nor, Nabilah (2017)
Throughout history, spinster characters have been given clashing portrayals in literature. Her famous representation in the classics, as seen within Miss Havisham (Great Expectations by Charles Dickens) and Emily Grierson (A Rose for Emily by William Faulkner); had been romantic wrecks who had channelled their desires and frustrations through the elements of grotesque. The modern spinster on the other hand, were projected to be promiscuos free-spirits through their self-autonomy and sexuality, as done with Bridget Jones (Bridget Jones’ Diary by Helen Fielding) and Samantha Jones (Sex and the City by Candace Bushnell). While given different treatments with the progression of time, spinsters had yet to escape the stereotypical traits inflicted upon them. The continuous appearance of stereotypical themes were found not only in Western narratives but also in its Eastern counterparts, as found within the short stories selected for this research. The similarity from different eras and cultural backgrounds inspires the question of how the individual spinster arrives to her stereotypical identity - as either romantic wrecks or promiscuous free-spirits. Believing in the need of a study that examines spinsters beyond the judgement of her society and culture as the Other, this research seeks to provide an inward investigation of spinsters as free individuals capable of shaping their own identity - reading them from the perspective of the Self. Such would indicate the evaluation of their beliefs and choices, which is best navigated by Jean Paul Sartre’s version of The Freedom of Choice. It is applied within the investigation of the characters’ relationships with men, as spinsters are commonly recognized as women who are without the association of husbands. The study of her perception in such relationships would reveal how the characters’ qualify into spinsterhood, as well as the acquisition of their general stereotypes. To achieve its purpose, this study aims to fulfil two objectives. The first is to identify the cause of the four spinster characters to be unmarried. The fulfilment of this leads towards the second and most impactual objective of this study, which is to explore the characters’ individual progression towards acquiring their identity as stereotypical spinsters. Both contain the direct address upon the characters’ heterosexual relationships with men, whether romantic or sexual. Textual analysis will be conducted as the characters’ related experiences, thoughts and choices are examined under the frames of anguish (whether of the future or past), bad faith and authenticity. Parallel to its intention to study spinsters from the inward perspective as the Self, this study scrutinizes the characters to reveal the employment of misdirection strategies (omission and emphasis, or ambiguity and vagueness) as well, as the types of denial (denial of facticity or transcendence) that they were experiencing. The use of these components within the framework would describe the spinster’s state of bad faith in detail, as it unravels the use of her consciousness to navigate herself against the situation within her spinsterhood. The completion of the analysis reveals the spinster character’s freedom in deciding the course of her actions, in contrast to the usual beliefs that her identity is the consequence of unfortunate circumstances and societal governance. The short stories used in this study are Cik Jamilah (by Melissa Maureen Rizal) and Sara and the Wedding (by Karim Raslan) from Malaysia; as well as The English Language Teacher’s Secret (by Catherine Lim) and Heat Wave (by Nalla Tan) from Singapore.